Perovskite solar cell based on small molecule doping and preparation method thereof
By introducing small equine uric acid molecules into the perovskite precursor solution, the problem of uneven phase distribution in FACs perovskite solar cells is solved, and high-quality thin films are formed, which improves the photoelectric conversion efficiency and stability of solar cells.
Patent Information
- Application Number
- CN202411269233.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-03-04
AI Technical Summary
The existing FACs perovskite solar cells have uneven phase distribution problems caused by crystallization rate, which affects device performance.
The equineuric acid small molecule additive is introduced into the perovskite precursor solution. Through acid-base reaction and hydrogen bonding with A-position cations, FACs are induced to crystallize simultaneously, forming a uniform A-site phase distribution, releasing stress, enhancing crystallinity and reducing lattice strain.
By doping small molecules with horseuric acid, the uneven phase distribution problem of perovskite films is solved, and high-quality films are formed, charge transfer efficiency is improved, and the photoelectric conversion efficiency and stability of solar cells are significantly improved.
Smart Images

Figure CN119562695A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of solar cells, in particular to a perovskite solar cell based on small molecule doping and a preparation method thereof. Background Art
[0002] Perovskite solar cells (PSCs) are an emerging next-generation photovoltaic cell that has attracted much attention due to its low-cost manufacturing process and excellent photoelectric performance. In the past decade, the photoelectric conversion efficiency (PCE) of PSCs has increased significantly from 3.8% to 26.7%, which is comparable to the development of silicon solar cells. FAPbI3 has the narrowest band gap (~1.48eV) among Pb-based perovskites due to its theoretical limit advantage, and its thermal stability is better than that of methylamine (MA)-based perovskites. However, the α phase of pure FAPbI3 is unstable, which is also a key factor that restricts its industrialization process. MA is usually used. + or Cs + Replace some FA + (Formamidine) is used to inhibit phase transition (Michael, S., Taisuke, M., Ji-Youn, Seo., et al., Cesium-containing triple cation perovskite solar cells: improved stability, reproducibility and high efficiency. Energy Environ. Sci. 9, 1989–1997 (2016)). However, MA is easily evaporated during annealing, and the residual MA + It will trigger thermal instability, causing the perovskite solar cell device to degrade faster. Compared with the traditional MA system perovskite, due to FA + and Cs + Due to the mismatch of ion size, formamidine-cesium perovskite (FA x Cs 1-xThe crystallization of the PbI3) system undergoes a more complex intermediate phase transition process, thereby inducing lattice distortion, phase separation behavior, and the appearance of defect centers, increasing the difficulty of preparing uniform perovskite films. At the same time, this composition usually forms a smaller grain size and has a large number of defects and PbI2 residues on its surface, which impairs device performance (Wang, J., Wang, K., Zhang, C., et al. Surface Cleaning and Passivation Strategy for Durable Inverted Formamidinium–Cesium Triiodide Perovskite Solar Cells. Adv. Energy Mater. 13, 2302169 (2023)).
[0003] Therefore, the method of introducing additive modification is more directly used to regulate the crystallization kinetics. Most researchers prefer to introduce additives or solvents with more coordinated active groups to improve the Pb-I cluster structure to achieve high performance of perovskite devices. For example, researchers recently used PbI2·NMP coordination to regulate the crystallization process of FA-Cs perovskite system. The adduct formed by solvent and Pb-I cluster is widely used to regulate the perovskite phase transition process and improve the perovskite crystal quality. The dynamic balance between the formation and dissolution of perovskite in dimethyl sulfoxide (DMSO) and DMSO&DMF leads to a sharp increase in the perovskite grain size. Qing et al. also showed that the synergistic effect of DMSO and MACl additives facilitated the crystallization of perovskite, resulting in single-crystal-like films with smooth surfaces and low defect density, thus providing efficient perovskite solar cells (Qing, J., Liu, X.-K., Li, M., et al. Aligned and Graded Type-II Ruddlesden–Popper Perovskite Films for Efficient Solar Cells. Adv. Energy Mater. 8, 1800185 (2018)).
[0004] Similarly, a small amount of MACl is introduced to regulate the perovskite crystallization process. MACl delays crystallization and induces the growth orientation of the crystal, but it does not completely solve the uncontrollable crystallization process caused by the different solubility between Cs and FA. Specifically, the low solubility of the inorganic component Cs will precipitate first, accelerating the nucleation crystallization at the top of the film, resulting in longitudinal phase separation of the film. Differences in crystallization dynamics lead to local heterogeneity of CsFA films with clustered crystals, which hinders charge transfer and increases recombination losses (Bai, Y., Huang, Z., Zhang, X., et al., Initializing film homogeneity to retardphase segregation for stable perovskite solar cells. Science. 378, 747-754 (2022)). Summary of the invention
[0005] The purpose of the present invention is to provide a perovskite solar cell based on small molecule doping and a preparation method thereof, so as to solve the problem of uneven phase distribution caused by the crystallization rate of the existing FACs perovskite solar cell.
[0006] The present invention is achieved in that:
[0007] A small molecule doped perovskite solar cell, whose structure includes, from bottom to top, a substrate, an electron transport layer, a perovskite layer, an interface modification layer, a hole transport layer and a top electrode layer; the perovskite solution used in preparing the perovskite layer is formed by doping hippuric acid molecules into a perovskite precursor solution.
[0008] The perovskite precursor solution contains ABX3 type perovskite material, wherein A is an alkali metal ion and an organic ion, the alkali metal ion is a Cs ion, the organic ion is a FA ion; B is a Pb ion; and X is one of the halogens. The perovskite precursor solution also contains MACl.
[0009] Preferably, the hippuric acid molecular concentration is 0.3-1 mg / mL.
[0010] Preferably, the perovskite solar cell is a NIP-type perovskite cell.
[0011] Preferably, the perovskite solar cells are normal bandgap and wide bandgap perovskite solar cells.
[0012] Preferably, the band gap of the perovskite solar cell is 1.53 to 1.60 eV.
[0013] Preferably, the perovskite solar cell system is FA x Cs 1-xPbI3; wherein the value range of x is 0.85~0.95.
[0014] Preferably, the substrate is one or more of ITO conductive glass, FTO conductive glass, flexible PET substrate, and flexible PEN substrate.
[0015] Preferably, the hole transport layer material is NiO X , PTAA, Spiro-OMeTAD, fullerene derivatives, phosphoric acid self-assembled molecules and nitrogen oxides.
[0016] Preferably, the material of the perovskite layer is an ABX3 type perovskite material; wherein A is two of alkali metal ions and organic ions, the alkali metal ions are Cs ions, and the organic ions are generally FA ions; B is Pb ions; and X is one of the halogens.
[0017] Preferably, the interface modification layer is one or more of phenethylammonium iodide, phenethylammonium bromide and phenethylammonium chloride.
[0018] Preferably, the electron transport layer material is C 60 , SnO2, TiO2, PCBM and zinc tin oxide or more.
[0019] Preferably, the top electrode layer is a metal electrode or a carbon material electrode; the metal electrode material includes one or more of gold, silver, aluminum and copper; the carbon material electrode includes one or both of graphite and carbon nanotubes.
[0020] The above-mentioned method for preparing a perovskite solar cell based on small molecule doping comprises the following steps:
[0021] (1) preparing an electron transport layer on a substrate by a spin coating process;
[0022] (2) Preparing a perovskite layer on the electron transport layer: adding a perovskite precursor solution to the weighed hippuric acid molecules and mixing them thoroughly to obtain a perovskite solution, and preparing the perovskite solution on the electron transport layer through an existing process to form a perovskite film, specifically: preparing the perovskite film by a two-step solution method, a spin coating method, a blade coating method, a spray coating method, etc., and then annealing on a heating table, the annealing temperature is 130-150°C, and the time is 20-25min; the perovskite precursor solution includes FAI, CsI, PbI2, and MACl;
[0023] (3) preparing an interface modification layer on the perovskite layer;
[0024] (4) preparing a hole transport layer on the interface modification layer;
[0025] (5) Prepare a top electrode layer on the hole transport layer.
[0026] The present invention introduces hippuric acid small molecule additives into the perovskite precursor solution (FACs perovskite system) to improve the preferential crystallization problem of Cs, control the overall crystallization process, and make the perovskite film crystallize uniformly from top to bottom, forming a high-quality perovskite film, thereby reducing defects. The present invention solves the phase distribution problem by doping small molecules with hippuric acid, in which the benzene ring can form a stable scaffold through π-π interaction, thereby being distributed on the surface and grain boundaries of the perovskite film to stabilize the interface structure. The carbonyl group and the O atom in the hydroxyl group in the molecule will react with Pb 2+ Coordination occurs, -NH and uncoordinated I - Hydrogen bonding occurs, which in turn passivates defects and accelerates the extraction of carriers. At the same time, the strong acid-base reaction and hydrogen bonding between the hippuric acid molecules and the A-site cations induce the simultaneous crystallization of FACs, resulting in a uniform A-site phase distribution and stress release. Its crystallinity is enhanced, the lattice strain is reduced, and a high-quality film is formed. At the same time, the formation of a uniform phase reduces the energy level difference between the upper and lower surfaces of the perovskite film, which is beneficial to charge transfer, and ultimately a high-performance FACs perovskite solar cell device is prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a schematic diagram of the structure of a perovskite solar cell based on small molecule doping provided by the present invention.
[0028] Figure 2 This is the JV curve of the perovskite solar cell prepared in Example 1.
[0029] Figure 3 It is a comparison chart of the photoelectric conversion efficiency, open circuit voltage, fill factor and short circuit current density of the perovskite solar cells prepared according to the method described in Comparative Example 1 and Examples 1 to 3.
[0030] Figure 4 This is the JV curve of the perovskite solar cell prepared in Comparative Example 1.
[0031] Figure 5 JV curves of the perovskite solar cells prepared in Comparative Examples 2 and 3. DETAILED DESCRIPTION
[0032] Combination Figure 1, the perovskite solar cell based on small molecule doping provided by the present invention, its structure includes from bottom to top: substrate (for example, ITO conductive glass), electron transport layer (for example, SnO2), perovskite layer, interface modification layer (for example, PEAI), hole transport layer (for example, Spiro-OMeTAD) and top electrode layer (for example, Au). When preparing the perovskite layer of the present invention, a low-concentration hippuric acid small molecule material is first doped in the perovskite precursor solution, and then the perovskite layer is prepared by conventional processes. The perovskite precursor solution contains ABX3-type perovskite materials, wherein A is an alkali metal ion and an organic ion, the alkali metal ion is a Cs ion, and the organic ion is generally a FA ion; B is a Pb ion; X is one of the halogens. Low-concentration hippuric acid small molecule materials are doped in the perovskite precursor solution, and the strong acid-base reaction and hydrogen bonding between the hippuric acid molecules and the A-site cations induce FACs to crystallize simultaneously, obtain a uniform A-site phase distribution, and release stress. Its crystallinity is enhanced and lattice strain is reduced, forming a high-quality film. At the same time, the formation of a uniform phase reduces the energy level difference between the upper and lower surfaces of the perovskite film, which is beneficial to charge transfer, and ultimately prepares a high-performance FACs perovskite solar cell device.
[0033] When preparing the perovskite layer, the perovskite film is formed by a two-step solution method, a spin coating method, a blade coating method, and a spray coating method. The present invention has no special provisions for the preparation of the perovskite layer, and a process well known to those skilled in the art can be used. Preferably, the spin coating method is used, and the other methods (such as blade coating, etc.) are not particularly limited, and methods well known in the art can be used.
[0034] The perovskite solar cell in the present invention is a general bandgap perovskite solar cell; the bandgap of the perovskite solar cell used is 1.53-1.60 eV. The present invention has no special requirements for the area of the general bandgap perovskite solar cell.
[0035] The substrate selected in the present invention is ITO conductive glass, FTO conductive glass, a flexible PET substrate or a flexible PEN substrate, and any structure well known to those skilled in the art can be used.
[0036] The top electrode layer selected in the present invention is a metal electrode or a carbon material electrode; the metal electrode material includes one or more of gold, silver, aluminum and copper; the selected carbon material electrode includes one or two of graphite and carbon nanotubes. The present invention has no special requirements for the thickness of the top electrode layer, which is well known to researchers in the field.
[0037] In the present invention, the top electrode layer is prepared by a thermal evaporation process. There is no special limitation on the thermal evaporation process, and the technology well known to those skilled in the art can be used.
[0038] In the present invention, the hole transport layer material used can be NiO X , PTAA, Spiro-OMeTAD, fullerene derivatives, phosphoric acid self-assembly molecules and nitrogen oxides; when the hole transport layer adopts two or more of the above, there is no special requirement for the ratio, and any proportion can be mixed. In addition, the present invention has no special requirements for the thickness of the hole transport layer, and a thickness familiar to those skilled in the art can be used. The present invention has no special provisions for the preparation of the hole transport layer, and a conventional spin coating method can be used.
[0039] In the present invention, the interface modification layer is generally an ammonium salt, which can be one or more of phenethylammonium iodide, phenethylammonium bromide and phenethylammonium chloride. If there are two or more, there is no special requirement for the ratio. There is no special requirement for the thickness, and the thickness well known to those skilled in the art can be used.
[0040] The electron transport layer material used in the present invention is C 60 , SnO2, TiO2, PCBM and zinc tin oxide, etc.; when two or more are selected, there is no special regulation on the ratio, and they can be mixed in any proportion. In addition, the present invention has no special requirements for the thickness of the prepared electron transport layer, and the thickness familiar to those skilled in the art can be used.
[0041] The present invention aims to introduce hippuric acid small molecule materials into the perovskite precursor solution, improve the crystallization kinetics of perovskite through the interaction between carbonyl and perovskite, provide nucleation sites for the crystallization of perovskite, and lead to uniform perovskite phase distribution. The efficient carrier extraction between perovskite and charge transport layer reduces V oc The loss and defect state density are reduced, which ultimately leads to a significant improvement in the short-circuit current and efficiency of solar cells. The method is simple and has a high repetition rate.
[0042] The perovskite solar cell of the present invention is described in detail below through examples, but the present invention is not limited to the following examples.
[0043] Example 1
[0044] (1) Using ITO conductive glass as a substrate, the substrate was ultrasonically cleaned using a cleaning agent, deionized water, and ethanol, then dried, and then plasma cleaned to remove residual organic matter on the surface and placed in a fume hood for later use.
[0045] (2) After diluting deionized water and SnO2 original solution in a volume ratio of 3:1, the diluted SnO2 solution is coated on the ITO surface of the substrate, annealed at 150° C. for 30 min, and then plasma cleaned to obtain an electron transport layer.
[0046] (3) The perovskite film was prepared by spin coating. 0.95mmol of FAI, 0.05mmol of CsI, 1mmol of PbI2, 0.15mmol of MACl and 0.5mg of hippuric acid molecules were mixed and dissolved in 1mL of DMF and DMSO mixed solvent (the volume ratio of DMF and DMSO was 4:1) to obtain a perovskite solution; 30μL of the perovskite solution was dripped on the electron transport layer, and then the film was formed by spin coating at a speed of 5000rpm for 30s. 160μL of anti-solvent was added 8s before the end, and annealed on a heating table at 150℃ for 20min to obtain a perovskite layer (the system is FA 0.95 Cs 0.05 PbI3).
[0047] (4) Dissolve 6 mg of phenethylammonium iodide in 1 mL of isopropanol to obtain a solution for use after the solution is completely dissolved; apply the obtained solution on the surface of the perovskite layer to obtain an interface modification layer.
[0048] (5) To 1 mL of Spiro-OMeTAD solution (72.3 mg of Spiro-OMeTAD powder dissolved in 1 mL of chlorobenzene solution), 17.5 μL of Li-TFSI solution (520 mg of Li-TFSI powder dissolved in 1 mL of acetonitrile solution) and 29 μL of TBP solution were added as dopants. The doped Spiro-OMeTAD solution was spin-coated on the interface modification layer to form a hole transport layer.
[0049] (6) Finally, the Au electrode is prepared to obtain a perovskite solar cell.
[0050] The obtained perovskite solar cell was placed under a standard sunlight (AM 1.5, 100 mW / cm 2 ) and measured its photoelectric performance, where the JV curve is as follows Figure 2 As shown in Figure 2, the short-circuit current density of the perovskite solar cell was measured to be 25.52 mA cm -2 , the fill factor is 83.11%, the open circuit voltage is 1.19V, and the photoelectric conversion efficiency is 25.24%.
[0051] Example 2
[0052] Compared with Example 1, the hippuric acid in this example is 0.3 mg / mL, and the rest is the same as Example 1.
[0053] Example 3
[0054] Compared with Example 1, the hippuric acid in this example is 1 mg / mL, and the rest is the same as Example 1.
[0055] Comparative Example 1
[0056] Reference Example 1, the difference is that after obtaining the electron transport layer, a perovskite layer is spin-coated on the electron transport layer, and the preparation process of the perovskite layer is as follows: 0.95mmol of FAI, 0.05mmol of CsI, 1mmol of PbI2 and 0.15mmol of MACl are mixed and dissolved in 1mL of DMF and DMSO solvent (the volume ratio of DMF and DMSO is 4:1) to obtain a perovskite solution. The rest is the same as Example 1, that is, this comparative example is a control group without hippuric acid small molecules.
[0057] The perovskite solar cell obtained in Comparative Example 1 was placed under a standard solar intensity (AM 1.5, 100 mW / cm 2 ) to test the photoelectric performance of perovskite solar cells, where the JV curve is as follows Figure 4 As shown by Figure 4 It can be seen that the open circuit voltage of the obtained perovskite solar cell is 1.17V, the fill factor is 80.65%, and the short-circuit current density is 24.88mA cm -2 , the photoelectric conversion efficiency is 23.52%.
[0058] Different samples were prepared according to Examples 1 to 3 and Comparative Example 1, and the photoelectric conversion efficiency, open circuit voltage, fill factor and short circuit current density of the ten samples were tested. The test results are as follows: Figure 3 shown. Figure 3 In the experiment, the concentrations of hippuric acid molecules were 0 mg / mL, 0.3 mg / mL, 0.5 mg / mL and 1 mg / mL, respectively. The average photoelectric conversion efficiency was 23.28%, 24.27%, 25.29% and 23.94%, the average open circuit voltage was 1.171 V, 1.175 V, 1.192 V and 1.193 V, the average fill factor was 80.46%, 81.46%, 83.14% and 81.25%, and the average short circuit current density was 24.71 mA cm -2 , 25.35mA cm -2 、25.54mA cm -2 and 24.71 mA cm -2 The perovskite solar cell of Example 1 corresponding to a concentration of 0.5 mg / mL has better performance and the best efficiency, mainly due to the significant improvement in open circuit voltage and fill factor. When the concentration exceeds 1 mg / mL, the V OC Significant decrease.
[0059] Comparative Example 2
[0060] Refer to Example 1, except that no MACl additive is introduced during the preparation of the perovskite solution.
[0061] Comparative Example 3
[0062] Refer to Example 1, the difference is that in the process of preparing the perovskite solution, 0.5 mg of hippuric acid small molecules are replaced with 0.5 mg of para-aminohippuric acid molecules.
[0063] The perovskite solar cell obtained in Comparative Example 2 is subjected to a standard solar intensity (AM 1.5, 100 mW / cm 2 ) to test the photoelectric performance of perovskite solar cells, where the JV curve is as follows Figure 5 Without the introduction of MACl additives, the device performance obtained after readjusting various processes was the worst, with a maximum PCE of only 20.6%.
[0064] The JV curve of the perovskite solar cell obtained in Comparative Example 3 is as follows: Figure 5 As shown. Figure 5 It can be seen that the open circuit voltage of the obtained perovskite solar cell is 1.15V, the fill factor is 81.02%, and the short-circuit current density is 23.10mA cm -2 , the photoelectric conversion efficiency is 21.52%. The carboxylate anion has strong electronegativity, while the amino group in the para position is positively charged, and a strong π-π interaction occurs between the molecules. In theory, it can better bind to the uncoordinated PbI2, thereby passivating defects and forming a high-quality film. The experimental results show that the open circuit voltage and short-circuit current density of the battery have decreased, so the overall photoelectric conversion efficiency has also decreased compared to Comparative Example 1. The inventor believes that the strong positive and negative properties of the aminohippuric acid molecule when combined with PbI2 destroy [PbI6] 4- The cubic octahedral structure causes the perovskite film to be unstable and its performance to deteriorate.
[0065] The above description is only the best implementation of the present invention. It is particularly pointed out that for ordinary technicians in this technical field, making several improvements and modifications without departing from the principle of the present invention are regarded as the protection scope of the present invention.
Claims
1. A perovskite solar cell based on small molecule doping, characterized in that: Its structure includes a substrate, an electron transport layer, a perovskite layer, an interface modification layer, a hole transport layer and a top electrode layer from bottom to top; the perovskite solution used in preparing the perovskite layer is formed by doping hippuric acid molecules into a perovskite precursor solution; the perovskite precursor solution contains ABX3 type perovskite materials, wherein A is an alkali metal ion and an organic ion, the alkali metal ion is a Cs ion, and the organic ion is a FA ion; B is a Pb ion; X is one of the halogens; and MACl is also included in the perovskite precursor solution.
2. The perovskite solar cell based on small molecule doping according to claim 1 is characterized in that: The hippuric acid molecule concentration is 0.3-1 mg / mL.
3. The small molecule doped perovskite solar cell according to claim 1, characterized in that: The substrate is one or more of ITO conductive glass, FTO conductive glass, flexible PET substrate, and flexible PEN substrate.
4. The perovskite solar cell based on small molecule doping according to claim 1 is characterized in that: The hole transport layer material is NiO X , PTAA, Spiro-OMeTAD, fullerene derivatives, phosphoric acid self-assembled molecules and nitrogen oxides.
5. The small molecule doped perovskite solar cell according to claim 1, characterized in that: The electron transport layer material is C 60 , SnO2, TiO2, PCBM and zinc tin oxide or more.
6. The small molecule doped perovskite solar cell according to claim 1, characterized in that: The interface modification layer is one or more of phenethylammonium iodide, phenethylammonium bromide and phenethylammonium chloride.
7. The small molecule doped perovskite solar cell according to claim 1, characterized in that: The band gap of perovskite solar cells is 1.53~1.60eV.
8. A method for preparing a perovskite solar cell based on small molecule doping according to claim 1, characterized in that: The steps include: (1) preparing an electron transport layer on a substrate by a spin coating process; (2) Preparing a perovskite layer on the electron transport layer: FAI, CsI, PbI2, MACl and hippuric acid molecules are mixed and dissolved in DMF and DMSO solvents to obtain a perovskite solution, and a perovskite film is prepared on the electron transport layer by a two-step solution method, a spin coating method, a blade coating method or a spray coating method, and then annealed on a heating table at a temperature of 130 to 150 ° C for 20 to 25 min; (3) preparing an interface modification layer on the perovskite layer; (4) preparing a hole transport layer on the interface modification layer; (5) Prepare a top electrode layer on the hole transport layer.
9. The method for preparing a perovskite solar cell based on small molecule doping according to claim 8, characterized in that: Perovskite solar cell system is FA x Cs 1-x PbI3; wherein the value range of x is 0.85~0.
95.
10. The method for preparing a perovskite solar cell based on small molecule doping according to claim 8, characterized in that: The substrate is one or more of ITO conductive glass, FTO conductive glass, flexible PET substrate, and flexible PEN substrate.